Enablers and barriers to adoption of sustainable silvopastoral practices for livestock production in Colombia - Chamorro-Vargas, Carol Tatiana; Morgan, Seth; Pantevéz, Heiber; Gomez, Manuel; Kennedy, Christina Marie; Kremen, Claire (Frontiers in Sustainable Food Systems, 2025)
In Latin America, the expansion of land for Extensive Cattle Ranching (ECR) is the leading driver of deforestation causing unsustainable levels of environmental degradation and social vulnerability to climate change extremes of drought or flood. Silvopastoral Systems (SPS) are a promising agroecological alternative to ECR. SPS combines trees and shrubs with forage grasses to enhance cattle production and landscape heterogeneity in this region. Despite strong evidence of SPS benefits (e.g., soil protection and recovery, increased cattle productivity and benefits to biodiversity), its adoption remains low. Previous work on how to scale out this practice has considered adoption as a binary option, without examining levels of adoption based on the amount (area) of SPS and types of practices adopted. This research aimed to assess how SPS can be scaled out by exploring the factors that influenced the number of hectares and component practices of SPS adopted by individual farmers to understand enablers and barriers. We used mixed effects linear models to analyze socio-economic survey data from 2,900 farms in Colombia collected over 9 years under the Sustainable Cattle Ranching (SCR) project (organized by The Nature Conservancy, CIPAV, FEDEGAN and Fondo Acción) combined with open access environmental information (8 spatial layers). The factors that had a positive significant effect on adoption were Payments for Ecosystem Services (PES), distance to closest SCR farm, presence of forest or watershed on the farm, and high levels of soil erosion. Water demand and hydric vulnerability (i.e., susceptibility to drought and flood) had a negative effect on adoption. These findings enhance knowledge of enablers and barriers for SPS adoption, including environmental constraints, thereby improving our understanding of pathways for scaling out agricultural transformation and shifting ECR to more sustainable alternatives.